Analisis Perbandingan Beban Transformator pada Gardu Induk Ranomuut antara Bulan Konsumsi Listrik Tinggi dan Rendah - Ruddy Juliando Pether Ransun; Sartje Silimang; Liliy S. Patras (Journal of Comprehensive Science, 2026)
This research aims to analyze the loading level of the power transformer at Ranomuut Substation by comparing transformer loads during months of low and high electricity consumption. The analysis was conducted to determine the variation of apparent power (S) and the percentage of transformer loading relative to its nominal capacity of 20 MVA. The data used were obtained from current and voltage measurements on the 70 kV and 20 kV sides during four observation months, namely June, July, March, and August. The calculation results show that in June and July, the transformer operated under low-load conditions with an apparent power of 10.09 MVA and a loading percentage of 50.48%. In March, the apparent power increased to 14.82 MVA with a loading level of 74.10%, indicating a high-load but still safe condition. Meanwhile, in August, the transformer reached the highest apparent power of 21.53 MVA with a loading level of 107.63%, which indicates an overload condition as it exceeded the nominal capacity. A comparison between the low-load and high-load months shows an increase in loading by 57.15%, reflecting a significant rise in electricity consumption in the Ranomuut Substation area, influenced by industrial activity and increased household electricity demand. Overall, the transformer still operates properly under both low and high loads; however, continuous monitoring and effective load management are required to prevent overloading during peak demand periods and to maintain system efficiency and equipment lifespan